Mindfulness dan Impulsive Buying Pada Dewasa Awal yang Melakukan Belanja Online Selama Pandemi Covid-19 - Farah Salisa; Risana Rachmatan; Intan Dewi Kumala; Novita Sari (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Pandemic of COVID-19 has led to an increase in use of e-commerce. Increased online shopping transactions lead to impulsive buying behavior for consumers who like to shop online. The large selection of products that are sold and purchased online in e-commerce makes people interested in online shopping. Impulsive buying is characterized by unplanned buying behavior. Mindfulness can control individual decisions to reduce intensity of impulsive buying behavior. If someone is not aware of buying the goods purchased, then shopping behavior can become something that is automatic and does not fulfill what is actually needed. The purpose of this study was to examine the relationship between mindfulness and impulsive buying in early adults who shopped online during COVID-19 pandemic. The research participants were 352 early adults in Aceh Province who had done online shopping. This study used quantitative correlation method. Data collection used Impulsive Buying Tendency Scale (IBTS) and Mindfulness Attention and Awareness Scale (MAAS). The results of Pearson's correlation analysis show a significant value (p) = 0.001 (p<0.05), indicates that there is relationship between mindfulness and impulsive buying in early adults who shop online during COVID-19 pandemic.